More than meets the eye: A case of synchronous ipsilateral clear cell renal cell carcinoma and urothelial carcinoma of the pelvicalyceal system and literature review - Symeonidis, Asterios; Tsikopoulos, Ioannis; Symeonidis, Evangelos N.; Tsifountoudis , Ioannis; Michailidis, Antonios; Tsantila, Ioanna; Gkekas , Chrysovalantis; Georgiadis , Christos; Malioris, Apostolos; Papathanasiou , Michail (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: The synchronous occurrence of renal cell carcinoma and urothelial carcinoma of the renal pelvis in the same kidney is extremely rare, although previously reported. With this study we aim to present our case and provide a literature review on this entity.Methods: An otherwise healthy 43-year-old military male with the chief complaint of left plank pain was seen in the office. Imaging revealed the presence of a 3.5 cm left renal mass. Left laparoscopic radical nephrectomy was performed for presumed renal malignancy. Pathology confirmed the presence of a clear cell RCC and revealed an area of low-grade UC arising from the ipsilateral renal pelvis, not visible in the preoperative imaging. Furthermore, a Pubmed database search in English language was conducted, up to June 2021, to identify the rate of simultaneous RCC and UC of the renal pelvis or ureter in RN specimen performed for presumed RCC or renal malignancy and subsequent management in these cases.Results: A total of 53 articles reporting on 56 patients with synchronous ipsilateral RCC and UC of the renal pelvis were identified, together with our case. Eight cases (14%) were initially managed with RN, thereby requiring further management of the ureteral stump. Of these, six (75%) were managed with distal ureterectomy, one (12.5%) with active surveillance of the ureteral stump, while one case (12.5%) did not report subsequent management. To our knowledge, we present the youngest patient recorded in the literature, with this histology combination presenting synchronously in the same kidney.Conclusions: Although uncommon, the final pathology report may reveal neoplasms of dissimilar histology that may involve the renal pelvis. It is crucial for urologists and pathologists to be vigilant of such cases during a solid renal mass workup. Additional therapeutic adjustments may be necessitated, derailing the initial treatment plan.